Criminological theory: the essentials - Tibbetts, Stephen G. (SAGE, 2019)
Preface -- Introduction to the book: an overview of issues in criminological theory -- Preclassical and classical theories of crime -- Modern applications of the classical perspective : deterrence, rational choice, and routine activities or lifestyle theories of crime -- Early positive school perspectives of criminality -- Modern biosocial perspectives of criminal behavior -- Early social structure and strain theories of crime -- The Chicago school and cultural and subcultural theories of crime -- Social process and learning theories of crime -- Social reaction and critical models of crime -- Feminist models of crime -- Life-course perspectives of criminality -- Integrated theoretical models and new perspectives of crime -- Glossary -- Index -- About the author